Same Bed, Different Dreams? Structural Factors and Leadership Characteristics of Central Government Agency Reform in China. Issue 4 (8th August 2019) - Ma, Liang; Christensen, Tom
ABSTRACT: The reorganization of government agencies can be studied as a pre-reform process in terms of the structural changes made, or as a post-reform process in terms of the effects of the reorganization. In this study of two mergers of agencies in China's central administration, we focus on structural features and the post-merger process, paying special attention to structural and cultural integration. Our qualitative analyses reveal that the National Health and Family Planning Commission (NHFPC) is considered to have been more successful in merging agencies and integrating functions than the State Administration for Press, Publications, Radio, Film and Television (SAPPRFT). We found that using physical arrangements and leadership features as explanatory variables generated helpful theoretical and policy implications for organizational architecture and public sector reforms.